PPolyHb protects myocardial H9C2 cells against ischemia-reperfusion injury by regulating the Pink1-Parkin-mediated mitochondrial autophagy pathway. Issue 1 (4th December 2019) - Zhu, Wenjin; Liu, Fang; Wang, Li; Yang, Bo; Bai, Yuwei; Huang, Yanzhi; Li, Yaru; Li, Wei; Yuan, Yuemin; Chen, Chao; Zhu, Hongli
Abstract: Mitochondrial dysfunction is a major contributory factor for myocardial ischemia-reperfusion (I/R) injury. It has been reported that Pink1-Parkin-mediated mitochondrial autophagy could effectively remove damaged mitochondria and excess ROS to ensure the stability of intracellular mitochondria. The present study was designed to evaluate whether the polymerized porcine haemoglobin (pPolyHb), a novel type of haemoglobin oxygen carrier, has an effect on I/R injury via regulating the Pink1-Parkin mediated mitochondrial autophagy pathway in myocardial H9C2 cells. The results revealed that pPolyHb could effectively reduce apoptosis and improve the survival rates of H9C2 cells. In addition, Pink1 and Parkin levels gradually decreased with pPolyHb reoxygenation. The inhibition of mitochondrial autophagy through mitochondrial-division inhibitor-1(mdivi-1) resulted in a decrease in anti-apoptotic protein Bcl-2 and an increase in pro-apoptotic protein Bax and CytC. In conclusion, pPolyHb has a protective effect on myocardial ischemia-reperfusion injury by regulating moderate mitochondrial autophagy.